Digital Reflections: Role of Social Media in Shaping Women's Self-Image and Mental Health - Nadaf, Zaffar Ahmad; Nazir, Usma; Behera, Santosh Kumar (Journal of Education Method and Learning Strategy, 2025)
This study aims to explore the impact of social media on women's self-image and mental health, examining how different social media platforms influence perceptions of body image, self-esteem, and psychological well-being. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology was used to conduct and report systematic reviews. A comprehensive search was conducted across multiple electronic databases, including PubMed, PsycINFO, Web of Science, and Google Scholar. The search strategy involved using specific keywords such as "social media," "self-image," "mental health," "women," and "body image." The analysis reveals a complex relationship between social media use and women's self-image and mental health. The results underscore the significant influence of social media on women's self-image and mental health. While the pervasive nature of idealized images on social media can negatively impact women's psychological well-being, there are also opportunities for these platforms to foster positive self-perception and community support. Future research should focus on identifying strategies to mitigate the adverse effects of social media while enhancing its potential for positive influence. Policymakers, educators, and mental health professionals must collaborate to develop interventions that promote healthy social media use and support women's mental health.